Complete Blood Count in Preoperative Assessment of Acute Appendicitis -A Different Aspect - Khawaja, Farukh Gulzar; Mahmood, Khalid; Siddiqi, Ubaid Ullah; Farooq, Muhammad Umer; Abdullah, Muhammad; Nayyar, Afsa (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the role of neutrophils to lymphocytes ratio in predicting the severity of acute appendicitis among patients managed at tertiary care hospital.Study design: Cross-sectional study.Place and Duration of Study: Department of Surgery Combined Military Hospital Rawalpindi, from Jan to Jun 2021.Methodology: Three hundred patients diagnosed with acute appendicitis by a consultant surgeon were included in the study. The neutrophil to lymphocyte ratio was calculated at the time of diagnosis. The severity of the appendix was assessed at the time of surgery and graded between grades 0 and IV, depending upon the gross clinical findings. The severity grade of acute appendicitis and other factors was associated with the neutrophil-to-lymphocytes ratio in all the patients.Results: Out of 300 operated patients with the clinical diagnosis of acute appendicitis, 169 (56.3%) were males, while 131 (43.7%) were females. The mean age of the study participants was 31.21 ± 2.127 years. Based on severity, 60 (20%) had grade 0, 100 (33.3%) had Grade-I, 86 (28.7%) had Grade-2, 35 (11.7%) had Grade-III, while 19 (6.3%) had a Grade-IV appendicitis. 192 (64%) had neutrophil-to-lymphocyte ratio < 4.6 while 108 (36%) had more than 4.6. Chi-square test revealed that severity of acute appendicitis and raised C-reactive protein had a statistically significant correlation with raised neutrophil to lymphocyte ratio (p-value